دراسة تحليلية لواقع الغذاء في سورية خلال 2011-2012 وآفاق الطلب على الغذاء - جحجاح محسن; صقر إبراهيم; اسماعيل ريم (Latakia University Journal -Biological Sciences Series, 2016)
يهدف البحث إلى التعرف على واقع الغذاء في سورية خلال الفترة 2011-2012، ومقارنته بالوضع قبل بدء الأزمة (2008-2010). وقد أظهرت الدراسة أن إجمالي المساحة المزروعة في سورية بلغت خلال الأزمة نحو 4479ألف هكتار، وبنقص بلغ نحو 323ألف هكتار عن فترة ما قبل الأزمة، وكذلك تناقص حجم الإنتاج الزراعي النباتي خلال نفس الفترة بمقدار 3081.2ألف طن ليسجل 11021.5ألف طن، إلا أن حجم المتاح من الغذاء النباتي والحيواني زاد بشكل عام خلال فترة الأزمة بمقدار 923.7ألف طن ليسجل 18704.1ألف طن. أما نصيب الفرد من الغذاء فقد نقص خلال فترة الأزمة بمقدار 8كغليسجل 864.8كغ، بينما كان قبل الأزمة 872.8كغ، أما فيما يتعلق بقيمة الفجوة الغذائية تبين أنها زادت خلال الأزمة بمقدار 640.5مليون دولار لتصل إلى 1727.2مليون دولار،وأخيراً بينت الدراسة أن الطلب على الغذاء سيزداد في سورية خلال الفترة 2016-2020 إذ سيبلغ 22832.5ألف طن عام 2020، وبالتالي فان حجم الإنتاج المحلي من الغذاء المطلوب تحقيقه في سورية عام 2020 سورية سيبلغ 18170.8ألف طن. The research aims to identify the reality of food in Syria during the 2011-2012 period and compared to the situation before the crisis (2008-2010). The study showed that the total cultivated area in Syria during the crisis amounted to about 4479 thousand hectares, and the total lack of 323 thousand hectares from the pre-crisis period, as well as the decreasing size of the vegetation of agricultural production during the same period increased by 3081.2 thousand tons to score 11021.5 thousand tons, However, the availability of vegetarian food and animal size increased overall during the period of crisis by 923.7 thousand tons to score 18704.1 thousand tons, With regard to per capita food shortage has been during the crisis period by 8 kg to score 864.8 kg while it was before the crisis 872.8 kg, With regard to the value of the food gap turned out to be increased during the crisis by 640.5 million dollars to up to 1727.2 million dollars,. And finally the study showed that the demand for food will increase in Syria during the period 2016-2020, as will 22832.5 thousand tons in 2020, so the size of the domestic production of Syria, to be achieved in 2020 will be 18170.8 thousand tons